Pengaruh Promosi dan Harga di media Sosial Media Tiktok Terhadap Keputusan Pembelian - Azis Rahman Hadi; Nurherawati (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze the influence of TikTok social media promotion and price on purchasing decisions of Kahf products among consumers in Tasikmalaya Regency. The rapid development of digital technology has changed marketing strategies, especially through social media platforms such as TikTok, which are considered effective in attracting consumer attention through creative and interactive content. In addition to promotional factors, price is also an important consideration in influencing consumer purchasing decisions. This research uses a quantitative approach with an associative research method. The population in this study consists of consumers who have purchased Kahf products online and actively use TikTok social media. Data collection was carried out through questionnaires distributed online. The collected data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics version 31. The results of this study are expected to show that TikTok social media promotion and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. This study is also expected to provide insights for companies in designing effective digital marketing strategies and determining appropriate pricing policies to increase consumer purchasing decisions toward Kahf products.